Komunikasi Kebijakan Program Satu Nagari Satu Event sebagai Media Promosi Pariwisata Kabupaten Tanah Datar - Dion Eriend; Athifa Nabila Risti; Ria Edlina; Gilang Surendra (CV. ITTC INDONESIA, 2025)
Satu Nagari Satu Event (SNSE) is one of the flagship programs of the Regent of Tanah Datar, aimed at promoting regional tourism through events grounded in local culture and traditional wisdom. The limited effectiveness of culture-based tourism promotion at the local level, along with the uneven participation of villages in the SNSE program, where only 46 out of 75 villages in Tanah Datar Regency have implemented it, indicates challenges in both the policy communication process and the diffusion of innovation at the village level. This study aims to analyze how the policy communication process of the SNSE program unfolds and to identify the supporting and inhibiting factors affecting its effectiveness as a tourism promotion medium in Tanah Datar Regency. The study employs a qualitative method with a descriptive approach and is grounded in Everett M. Rogers’ Diffusion of Innovation theory. Data were collected through in-depth interviews, moderate participant observation, and documentation. Data analysis was conducted through data reduction, data display, and thematic conclusion drawing. The findings reveal that SNSE policy communication operates through two primary patterns: a formal, regulatory channel grounded in Regent Regulation of Tanah Datar No. 22 of 2022, and an informal, participatory channel facilitated through village deliberations and digital media. The innovation adoption process is uneven, with some villages acting as early adopters due to strong resource readiness and social support, while others fall into the late majority or approach the laggard category due to limited capacity and low levels of policy literacy. Nevertheless, the SNSE program has proven effective in increasing community participation, strengthening local identity, and fostering culture-based creative economic growth.